THE ARMY AUDIT AGENCY GOES PROFESSIONAL. - Simpson, Clark L. (The Accounting Review, 1955)
The article focuses on the Army Audit Agency. The Army Audit Agency of the Office of the Comptroller of the Army, is a unique organization of the U.S. Government. Prior to and during World War II, the auditing functions were carried on in the various services of the Army but shortly after the conclusion of World War II, it became apparent that a consolidation of all audit functions under one head would be desirable. As a natural consequence, the Army Audit Agency became a part of the Office of the Comptroller. A former member of Accounting Systems Division was brought in as Deputy Chief to direct the technical operations. His introduction of streamlined professional auditing has been a boon to industry and a very necessary aid to improved Army management. The progress made in a short period has been most amazing. Although the Army Audit Agency was operating as a professional staff of auditors, the pressure of completing the necessary work in turning out audit reports was so great that little effort was expended on staff training or on-the-job training.